The Use of Smart and Topsis Methods in Decision Making Systems for Prioritizing Screen Printing Production - Panggabean, Jonas Franky R; Harahap, Leliana; Sirait, Kamson; Situmorang, Sutrisno; Purba, Sartika Dewi (Marqcha Institute, 2024)
Prioritization in screen printing production is a challenge for companies to improve efficiency and product quality, especially in conditions involving various conflicting criteria. This research aims to develop a decision-making system that can optimize the prioritization of screen printing production by using the SMART method for criteria weighting and the TOPSIS method for alternative analysis. The SMART method is used to assign weights to relevant criteria, while the TOPSIS method is used to evaluate and rank alternatives based on the relative distance to positive and negative ideal solutions. The results show that alternative B has the highest ranking with a preference index value of 0.587, which reflects the optimal combination of cost, time, quality, market demand, and resources. The implication of these findings is that combining the two methods can provide more objective and measurable decisions in the management of screen printing production, but further testing is needed on a wider scale and by considering dynamic external factors. This research opens up opportunities for the development of more adaptive systems in production decision-making in the screen printing industry.